Validation of A2DS2 Score as Predictor of Pneumonia among Patients Hospitalized for Acute Ischemic Stroke - Nababan, Toman; Pitoyo, Ceva Wicaksono; Harris, Salim; Rumende, Cleopas Martin (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Pneumonia is the leading cause of morbidity and mortality in acute ischemic stroke patients admitted to hospital. Thus required a valid scoring system which is easy to apply, to predict and stratify the risk of pneumonia in patients with acute ischemic stroke. This study aimed to assess the performance of calibration and discrimination of A2 DS2 score in predicting the incidence of pneumonia in patients with acute ischemic stroke. Methods. A retrospective cohort study was conducted among adult acute ischemic stroke patients who are hospitalized in Cipto Mangunkusumo Hospital, Jakarta. Age, atrial fibrillation, dysphagia, sex (male), and stroke severity (rated with National Institute of Health Stroke Scale/NIHSS) were obtained at the beginning of admission. The subjects were followed up for up to seven days after the onset of ischemic stroke to assess the outcome (pneumonia). Calibration properties of the A2 DS2 score were assessed by Hosmer-Lemeshow test and calibration plot. Discrimination properties of the A2 DS2 score were assessed by the area under the curve (AUC). Results. A total of 281 subjects were followed up. The incidence of pneumonia in acute ischemic stroke patients was observed in 118 patients (42%). Hosmer Lemeshow test of A2 DS2 score showed p = 0,222 and calibration plot showed r = 0,982. Discrimination of A2 DS2 score was shown by the AUC value of 0,885 (95% CI 0,845-0,924). Conclusion. The A2 DS2 score has a good calibration and discrimination performance in predicting the incidence of pneumonia in patients with acute ischemic stroke.